Photovoice Communication on Elementary School Children's Anxiety in Rote Facing Vaccination and Its Impact on COVID-19 Vaccination Coverage - Mas’amah Mas’amah; Apris A. Adu; Marylin. S. Junias (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The importance of vaccines lies in their ability to enhance the immune system. However, for elementary school children, vaccination programs often evoke fear, particularly due to the use of needles and the need for the program to be conducted twice. Teachers, as parental figures at school, are expected to play a critical role in communication to strengthen children's mental resilience, enabling them to participate in the vaccination program. This study aims to examine the use of photovoice communication to address elementary school children's anxiety about vaccination in Rote and its impact on COVID-19 vaccination coverage. Methods: This qualitative study employed the photovoice technique as the primary method for data collection. Results: The findings reveal that collaboration between teachers, healthcare workers, and parents in communicating about the vaccination program can foster supportive communication among students, strengthening their mental resilience. Synergistic communication between teachers, parents, and healthcare workers, along with providing incentives for vaccinated students, effectively reduces fear and contributes to the success of the vaccination program for children. Conclusion: The study concludes that synergistic communication between teachers, parents, and healthcare workers is a key strategy in reducing children's fear and ensuring the success of vaccination.